Dietary moderately oxidized oil activates the Nrf2 signaling pathway in the liver of pigs - Varady, Juliane; Gessner, Denise K.; Most, Erika; Eder, Klaus; Ringseis, Robert; Justus Liebig University Giessen (My University, 2012)
ABSTRACT: BACKGROUND: Previous studies have shown that administration of oxidized oils increases gene expression and activities of various enzymes involved in xenobiotic metabolism and stress response in the liver of rats and guinea pigs. As these genes are controlled by nuclear factor erythroid-derived 2-like 2 (Nrf2), we investigated the hypothesis that feeding of oxidized fats causes an activation of that transcription factor in the liver which in turn activates the expression of antioxidant, cytoprotective and detoxifying genes. METHODS: Twenty four crossbred pigs were allocated to two groups of 12 pigs each and fed nutritionally adequate diets with either fresh rapeseed oil (fresh fat group) or oxidized rapeseed oil prepared by heating at a temperature of 175degreesC for 72 h (oxidized fat group). RESULTS: After 29 days of feeding, pigs of the oxidized fat group had a markedly increased nuclear concentration of the transcription factor Nrf2 and a higher activity of cellular superoxide dismutase and T4-UDP glucuronosyltransferase in liver than the fresh fat group (P < 0.05). In addition, transcript levels of antioxidant and phase II genes in liver, like superoxide dismutase 1, heme oxygenase 1, glutathione peroxidase 1, thioredoxin reductase 1, microsomal glutathione-S-transferase 1, UDP glucuronosyltransferase 1A1 and NAD(P)H:quinone oxidoreductase 1 in the liver were higher in the oxidized fat group than in the fresh fat group (P < 0.05). Moreover, pigs of the oxidized fat group had an increased hepatic nuclear concentration of the transcription factor NF-kappaB which is also an important transcription factor mediating cellular stress response. CONCLUSION: The present study shows for the first time that administration of an oxidized fat activates the Nrf2 in the liver of pigs which likely reflects an adaptive mechanism to prevent cellular oxidative damage. Activation of the NF-kappaB pathway might also contribute to this effect of oxidized fat.
Keywords: Nrf2 signaling pathway induction; oxidized oils; pig liver; xenobiotic metabolism; stress response; ddc:570